Endeavour. Series 1 [videorecording (DVD)] - Evans, Shaun, 1980-; Allam, Roger (WGBY DVD Collection, 2013)
The continuing stories of rookie Constable Morse. The young Endeavour Morse is on the case, before his signature red Jaguar, but with his deductive powers already running in high gear.